Circular economy and input-output impacts of phasing out the coal sector in Muğla, Türkiye: a regional just transition perspective - Kizilkaya, Simay; Acar, Sevil; Ozenc, Bengisu (FRONTIERS MEDIA SA, 2026)
This study evaluates the economic and environmental implications of phasing out the coal sector and discontinuing subsidies for both coal mines and coal-fired power plants in Mu & gbreve;la, T & uuml;rkiye, with a focus on key metrics such as output, value-added, employment, and greenhouse gas (GHG) emissions. The analysis proceeds in two distinct phases. Initially, it explores the direct effects of removing investment incentives for coal mining and capacity payments to thermal power plants within the electricity market capacity mechanism on regional economic indicators and environmental outcomes. Subsequently, it examines three alternative scenarios wherein these subsidies are used as a just transition fund and redirected towards greener energy technologies, investments in the circular economy within selected industries, and lower-carbon sectors in the regional context. This two-pronged approach facilitates a comparative evaluation of the costs and benefits of subsidy reform from the perspective of a just transition. The findings aim to guide regional development strategies that balance economic growth with climate mitigation objectives. By elucidating the distributional and environmental trade-offs associated with coal subsidy removal and the reallocation of funds towards sustainable investments, the study provides valuable insights for designing policies that support equitable decarbonization and promote circular economies at the local level.
Keywords: circular economy; coal subsidies; GHG emissions; green energy technologies; just transition; regional input-output analysis; EMPIRICAL-EVIDENCE; ENERGY TRANSITION; TABLES; FLQ; Science & Technology - Other Topics; Environmental Sciences & Ecology